Effect of carbonic maceration (CM) on mass transfer characteristics and quality attributes of Sanhua plum (Prunus Salicina Lindl.). (January 2018) - An, Kejing; Wu, Jijun; Tang, Daobang; Wen, Jing; Fu, Manqin; Xiao, Gengsheng; Xu, Yujuan
Abstract: Sanhua plum is an important tropical fruit in China with epicuticular wax and dense pulp, causing difficulties for dehydration and sucrose penetration. Carbonic maceration (CM) is an efficient and low cost technology, which can increase the mass transfer rate during candying/drying process and improve the quality indices of Sanhua plum. The results showed that CM treatment could disturb wax layer, produce porous structure and increase the permeability of cell membrane, which could significantly increase the rate of sugar intake and water loss during candying and drying processes. The sugar intake rate can be increased by 82.52 ± 5.38% and total drying time can be shortened by 39.47 ± 2.24%. In addition, CM could help to overcome the plant extraction barrier and enhance the active components content. The lower pH environment and inactivation of polyphenol oxidase (PPO) and peroxidase (POD) were also beneficial to the stability of phenol compounds, thus the increase of individual phenolics retention and antioxidant activity of Sanhua plum. The total anthocyanins, phenolics, flavonoids and the results of the ABTS assay were increased by 14.91–29.63%, 3.95–16.93%, 11.10–23.10%, and 2.10–56.71%, respectively after CM treatment. Therefore, CM is a very promising pretreatment for fruits and vegetables dehydration. Highlights: CM is a favorable pretreatment for candying/drying of Sanhua plum. CM could increase the mass transfer rate of sugar and moisture during candying/drying process. CM could improve the individual phenolics content and antioxidant activity of Sanhua plum.